Consumer Preferences toward Goat Milk - M. Zul Mazwan; Yohana Agustina; Jangkung Handoyo Mulyo; Lestari Rahayu Waluyati (Universitas Muhammadiyah Malang, 2021)
The high level of business competition in this current globalization requires companies to produce quality products. Among the efforts of product improvement is through understanding consumer preferences. This study aims to identify consumer preferences of several attribute combinations of goat milk branded Bumiku Hijau, Yogyakarta. Conjoint analysis with pairwise-comparison was employed in this study. The combination of attributes analyzed were price, flavor variant, types of milk, and packaging. Results showed that the best combination results were obtained on stimuli number 13 with a total usability value of 3.709, which was 0.356 on the product price. The chocolate flavor variant attributes to the largest total usability value of 0.166. Based on the type of milk, the total usability value of powdered milk (skim) is 0.073, and the highest usability value was obtained through carton packaging (200gr) of 0.077. Consumers favored powdered goat milk products with new flavor variants that suit teenagers and adults. They also want 100 gr product packaging as it is easier to measure and consume.